Penerapan Konsep Earned Value Analysis terhadap Kinerja Biaya dan Waktu pada Proyek Pembangunan (Studi Kasus Proyek Pembangunan Gedung Terminal Pariwisata) - Purnomo, Dimas Aji ; Prisilia, Harliwanti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
The development of construction projects is currently increasingly large and complex both in terms of physical and cost. In this case the project planning and control is applied to the construction of the Integrated Tourism Terminal Building which has a total price of Rp. 12,904,970,589.17 with a implementation period of 154 calendar days. One alternative that can be used in an effort to overcome the constraints on this project is the "Earned Value" method. The concept of earned value is one of the tools used in managing projects that integrate costs and time. The purpose of this study is to determine the cost and time performance, estimated costs and time at the end of project completion and the factors that cause project delays or progress. The results of the analysis known at the end of the project review in the 20th week, the project schedule performance (SPI) was 1,19 which meant that the project's performance was faster than planned. While in terms of cost performance it can be concluded that the costs incurred are greater than the plan, this is indicated by the CPI value of 0,45. If the project performance trend is at the end of the 20th week review, based on this condition, the estimated total cost to be spent is Rp. 13,463,188,080 where the figure is far greater than the project budget of Rp. 12,904,970,242. When viewed from the estimated time of completion of the project is 130 days which means faster than planned time of 154 days.